Hair Cortisol in Sheltered Cows and Its Association with Other Welfare Indicators - Sharma, Arvind (Animals (Basel), 2019)
SIMPLE SUMMARY: Hair cortisol concentrations are measured for the assessment of long-term stress in animals. The objective of this study was to assess the levels of stress in retired, abandoned and unproductive cows housed in traditional shelters through the measurement of their hair cortisol levels. The study further aimed to explore the association of the hair cortisol concentrations with other cow and resource-based welfare indicators. High hair cortisol levels were associated with dung lying in the sheds, low dry bulb temperature and shelters having little access to the yards. At the cow level, high hair cortisol levels were associated with injuries on the joints and body, dehydration, old age, and low body hair loss level. The study concluded that hair cortisol is an effective tool to assess stress levels in cows under field conditions. ABSTRACT: India, the country with the largest population of dairy cows in the world, has a policy of retiring abandoned and non-lactating cows in shelters, but the level of provision for their welfare in these shelters is unclear. Cows in 54 shelters across India were assessed for historic evidence of physiological stress, through determination of hair cortisol in 540 samples from 10 cows in each shelter by enzyme immunoassay. Animal-based and shelter resource-based welfare measures were recorded and correlations with the hair cortisol investigated by multivariable analysis. High hair cortisol concentrations were associated with dung in the lying area of the cowshed, a low dry bulb temperature there and little cow access to yards, as shelter-based variables. At a cow level, high hair cortisol concentrations were associated with dirty flanks, hock joint ulceration, carpal joint injuries, body lesions, dehydration, an empty rumen, old age, and low levels of body hair loss. Hair cortisol level promises to be an effective biomarker of stress in cows when conducting studies under field conditions.